Pengaruh Kualitas Produk Terhadap Loyalitas Konsumen Melalui Kepuasan Konsumen Pada Perusahaan Shopee - Liana, Yuyuk; Putri, Intan; Djafri, Taufik; Priyo, Didik (Ecobuss, 2024)
This study aims to determine the effect of Product Quality on Consumer Loyalty through Consumer Satisfaction. This study uses primary data whose data collection uses a questionnaire. In this study, researchers used the Research Instrument Test (Validity Test, Reliability Test), SEM PLS, Model Accuracy Test (R-Square, Hypothesis Test) with the help of SMART PLS 4. The population in this study were all STIE Malangkucecwara Management Department students totaling 100. The results of the research obtained using the t test show that Product Quality has a significant positive effect on Customer Satisfaction with a result of 0.000, Product Quality has no significant positive effect on Customer Loyalty with a result of 0.070, and Customer Satisfaction has a significant positive effect on Customer Loyalty with a result of 0.000. Keywords: Product Quality, Consumer Loyalty, Consumer Satisfaction.